PENGGUNAAN ALAT PERAGA PIRAMIDA KELAJUAN DAN TANGGA KONVERSI UNTUK MENINGKATKAN PEMAHAMAN MENGHITUNG KONVERSI SATUAN - Dian Kusmaharti; Maria Christina Sri Sunarsih (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract : The rationale for implementing classroom action research is based on the observations and experiences of researchers during teaching at the Dukuh Public Elementary School dated I / 424 Surabaya, which states that for grade V students still have difficulty in carrying out mathematical calculation processes, especially calculation of unit conversion. In this research activity, researchers used two types of teaching aids as teaching media namely speed pyramids and conversion ladders with the aim of increasing students' understanding in mathematical unit conversion calculations. The results of this study indicate that the implementation of improved learning using the speed pyramid and conversion ladder in the first cycle runs quite well with an average value of 3.6 (on a scale of 1-5); student learning achievement in understanding concepts and mathematical calculations for unit conversion material is categorized sufficient, with a value of 79.28 (on a scale of 1-100); and student learning outcomes obtained an average of 75 with a percentage of completeness of 82%. In the second cycle, the implementation of improved learning using the speed pyramid and conversion ladder went well with an average value of 4.3 (on a scale of 1-5); student learning achievement in understanding concepts and mathematical calculations for unit conversion material is categorized sufficient, with a value of 86.79 (on a scale of 1-100); and student learning outcomes obtained an average of 87.5 with 97% completeness percentage. Keywords: student understanding, learning achievement, learning outcomes, speed pyramid, conversion steps Abstrak: Dasar pemikiran dilaksanakannya penelitian tindakan kelas ini berdasarkan hasil pengamatan dan pengalaman peneliti selama mengajar di Sekolah Dasar Negeri Dukuh Menanggal I/424 Surabaya, yang menyatakan bahwa untuk siswa kelas V masih mengalami kesulitan dalam melakukan proses perhitungan matematika khususnya perhitungan konversi satuan. Dalam kegiatan penelitian ini, peneliti menggunakan dua jenis alat peraga sebagai media mengajar yaitu piramida kelajuan dan tangga konversi dengan tujuan untuk meningkatkan pemahaman siswa dalam melakukan perhitungan konversi satuan secara matematis. Hasil penelitian ini menunjukkan bahwa pelaksanaan perbaikan pembelajaran menggunakan piramida kelajuan dan tangga konversi pada siklus I berjalan cukup baik dengan nilai rata-rata 3,6 (dalam skala 1-5); prestasi belajar siswa dalam memahami konsep dan perhitungan matematis untuk materi konversi satuan dikategorikan cukup, dengan nilai 79,28 (dalam skala 1-100); dan hasil belajar siswa diperoleh rata-rata 75 dengan persentase ketuntasan 82%. Pada siklus II, pelaksanaan perbaikan pembelajaran menggunakan piramida kelajuan dan tangga konversi berjalan baik dengan nilai rata-rata 4,3 (dalam skala 1-5); prestasi belajar siswa dalam memahami konsep dan perhitungan matematis untuk materi konversi satuan dikategorikan cukup, dengan nilai 86,79 (dalam skala 1-100); dan hasil belajar siswa diperoleh rata-rata 87,5 dengan persentase ketuntasan 97%. Kata kunci: pemahaman siswa, prestasi belajar, hasil belajar, piramida kelajuan, tangga konversin